Breast cancers arising in subjects with germline BRCA1 or BRCA2 mutations: Different biological and clinical entities with potentially diverse therapeutic opportunities - Zattarin, Emma; Taglialatela, Ida; Lobefaro, Riccardo; Leporati, Rita; Fucà, Giovanni; Ligorio, Francesca; Sposetti, Caterina; Provenzano, Leonardo; Azzollini, Jacopo; Vingiani, Andrea; Ferraris, Cristina; Martelli, Gabriele; et al. (Critical reviews in oncology/hematology, 2023)
Breast cancers (BCs) arising in carriers of germline BRCA1 and BRCA2 pathogenic variants (PVs) have long been considered as indistinguishable biological and clinical entities. However, the loss of function of BRCA1 or BRCA2 proteins has different consequences in terms of tumor cell reliance on estrogen receptor signaling and tumor microenvironment composition. Here, we review accumulating preclinical and clinical data indicating that BRCA1 or BRCA2 inactivation may differentially affect BC sensitivity to standard systemic therapies. Based on a different crosstalk between BRCA1 or BRCA2 and the ER pathway, BRCA2-mutated Hormone Receptor-positive, HER2-negative advanced BC may be less sensitive to endocrine therapy (ET) plus CDK 4/6 inhibitors (CDK 4/6i), whereas BRCA2-mutated triple-negative breast cancer (TNBC) may be especially sensitive to immune checkpoint inhibitors. If validated in future prospective studies, these data may have relevant clinical implications, thus establishing different treatment paths in patients with BRCA1 or BRCA2 PVs. [Display omitted] •BRCA1 and BRCA2 proteins have only partially overlapping biological functions.•Mutations in BRCA1 or BRCA2 predispose to different Breast Cancers (BC) subtypes.•BRCA2-mutated BCs have a more inflamed tumor microenvironment.•Endocrine therapy plus CDK4/6i is less effective in BRCA2-mutated BC patients.•Immune checkpoint inhibitors are more effective against BRCA2-mutated neoplasms.